Does Hospital Volume Affect Outcomes in Spine Surgeries? A Systematic Review. Issue 7 (August 2019) - Adkins, Zachary B.; Malik, Azeem T.; Jain, Nikhil; Yu, Elizabeth; Kim, Jeffery; Khan, Safdar N.
Abstract : Study Design: Systematic review. Objective: To assess the impact of hospital volume on postoperative outcomes in spine surgery. Summary of Background Data: Several strategies have recently been proposed to optimize provider outcomes, such as regionalization to higher volume centers and setting volume benchmarks. Materials and Methods: We performed a systematic review examining the association between hospital volume and spine surgery outcomes. To be included in the review, the study population had to include patients undergoing a primary or revision spinal procedure. These included anterior/posterior cervical fusions, anterior/posterior lumbar fusions, laminectomies, discectomies, spinal deformity surgeries, and surgery for spinal malignancies. We searched the Pubmed, OVID MEDLINE (1966–2018), Google Scholar, and Web of Science (1900–2018) databases in January 2018 using the search criteria ("Hospital volume" OR "volume" OR "volume-outcome" OR "volume outcome") AND ("spine" OR "spine surgery" OR "lumbar" OR "cervical" OR "decompression" OR "deformity" OR "fusions"). There were no restrictions placed on study design, publication date, or language. The studies were evaluated with respect to the quality of methodology as outlined by the Grading of Recommendations Assessment, Development, and Evaluation system. Results: Twelve studies were included in the review. Studies were variable in defining hospital volume thresholds. Higher hospital volume was associated with statistically significant lower risks of postoperative complications, a shorter length of stay, lower cost of hospital stay, and a lower risk of readmissions and reoperations/revisions. Conclusions: Our findings suggest a trend toward better outcomes for higher volume hospitals; however, further study needs to be carried out to define objective volume thresholds for specific spine surgeries for hospitals to use as a marker of proficiency.